Role of Mosque for Human Resource Development - Mahmud, Imran; Rawshon, Shahriar; Rahman, Md Jahidur (IIUC Studies, 2015)
In this research, an attempt was made to highlight the role of mosque to help build an Islamic HR environment in the society from moral and spiritual perspectives. It also focused on an extensive strategy to be applied by the concerned business people for Islamic HR practice in the organization effectively. If certain contents of HR practice were discussed in the jamat or the Friday khutbah at the Mosque addressing the terms Islamic HR practice would reflect the mind of the people working in different sectors. The research outlined here, if implemented, the Islamic HR would surely function as an effective means of building the stable business and the Islamic HR practice in the society. That type of step is an immense need in the age of the moral and spiritual crises when there is not enough scope to know that information about Islamic practice in business. The survey was based on primary and secondary data both. And this research WAS is developed in the context of Quran and Sunnah. The research is WAS based on mainly the Bangladesh perspective which reach that the 50% respondents strongly agreed that they would like to know about the Islamic Human Resource Management in the mosque where 70% respondents thought that the Mosque is a place for not only prayers but also a training centre of Islamic values. Another interesting outcome was 50% respondents are strongly agreed that it is important to bring Islamic scholars cum employers to share their knowledge about different disciplines at the mosque. Such a Mosque can help the Muslims to learn the views and thoughts of Islam and that can help the people live harmoniously and peacefully, and achieve salvation from Allah in the their life hereafter. IIUC Studies Vol.9 December 2012: 279-292